2018
DOI: 10.18502/kls.v4i4.2297
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Correlated to Work Fatigue of Hospital Nurses in Bandar Lampung

Abstract: Work fatigue is a symptom correlated to a decrease in work efficiency and skills and an increase in boredom and anxiety. If hospital nurses suffer work fatigue, they will be unable to perform at their best to care for patients, and this will reduce their productivity in providing services. This study aimed to identify the factors correlated to the work fatigue of hospital nurses in Bandar Lampung. This study had a crosssectional design. The study population included 247 respondents, and the final study sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
2
2
0
4
Order By: Relevance
“…The result of this research supported the previous research result which revealed that age has significant effect on work fatigue (Atiqoh et al, 2014;Bongakareng, Layuk, Pesak & Danial, 2019;Rahmawati & Tualeka, 2019). This research result was not in line the research conducted by Putri (2018), Saftarina et al (2018), and Yogisutanti et al, (2020) that there was no relationship between age and work fatigue (8).…”
Section: The Effect Of Age On Work Fatiguesupporting
confidence: 66%
See 1 more Smart Citation
“…The result of this research supported the previous research result which revealed that age has significant effect on work fatigue (Atiqoh et al, 2014;Bongakareng, Layuk, Pesak & Danial, 2019;Rahmawati & Tualeka, 2019). This research result was not in line the research conducted by Putri (2018), Saftarina et al (2018), and Yogisutanti et al, (2020) that there was no relationship between age and work fatigue (8).…”
Section: The Effect Of Age On Work Fatiguesupporting
confidence: 66%
“…The results were at the same track with a research done by Bongakaraeng et al (2019) which stated that there was an effect of job tenure on working fatigue. The findings obtained by Saftarina et al (2018) and Putri (2018) also supported this research results as they found that job tenure had a significant relationship with working fatigue (p = 0.041). The longer job tenure obtained a positive effect as the workers get more experiences; on the other hand, it brought a negative effect as the fatigue and boredom increased (Rahmawati & Tualeka, 2019).…”
Section: The Effect Of Job Tenure On the Working Fatiguesupporting
confidence: 62%
“…Gejala lain yaitu meningkatnya kecemasan, menurunnya ingatan, reaksi lambat, berkurangnya motivasi kerja dan meningkatnya kesalahan dalam bekerja (Gabriel & Dinges, 2018). Penelitian lain menyatakan bahwa kelelahan kerja ditandai oleh penurunan efisiensi dalam pekerjaan, ketrampilan dan meningkatkan kebosanan dan kecemasan (Saftarina, Mayasari, & Vilia, 2018). Para pekerja sering mengalami ketidaknyamanan pada system musculoskeletal dan gangguan kesehatan lain (Nag, Vyas, & Nag, 2016).…”
Section: Hasil Dan Pembahasanunclassified
“…Research (Dimkatni, Sumampouw Jufri, & Manampiring, 2020)conducted on 126 nurses who worked in the IGD, ICU, and inpatients at the Bitung Hospital and Budi Mulia Bitung Hospital showed that 66.9% experienced moderate fatigue and 1.7% experienced high fatigue. Research conducted on 153 nurses in the inpatient room of Bandar Lampung Hospital showed that the most experienced fatigue was 75.8% (Saftarina, Mayasari, & Vilia, 2016). Fatigue is a common complaint that affects nurse performance.…”
Section: Introductionmentioning
confidence: 99%